Modernizing the Charitable Sector through Artificial Intelligence: Enhancing Efficiency and Impact - Elamin, Mustafa Osman I. (Journal of Ecohumanism, 2024)
The proposed research explores the transformative potential of artificial intelligence (AI) in modernizing the charitable sector. Initiative aims to address critical gaps in program delivery, resource allocation, and impact assessment, ultimately enhancing the efficiency and effectiveness of humanitarian aid. The study argues that AI can revolutionize disaster response by predicting natural disasters, improve educational outcomes through personalized learning platforms, and enhance public health monitoring by forecasting disease outbreaks. Furthermore, AI can optimize food distribution systems, reducing waste and ensuring timely delivery. The research also emphasizes the urgent need to develop a digital safety framework to protect children and youth from online risks, exacerbated by the rapid proliferation of digital technologies. The methodology includes comprehensive data collection from various sectors, followed by the development and testing of AI models tailored to specific needs, such as disaster prediction and personalized education. The study also involves stakeholder engagement to ensure the practical applicability and ethical implementation of AI solutions. Expected results include resource use, improved program impact, a safer digital environment for vulnerable populations. The project aims to set a precedent for the integration of AI in the charitable sector.